Dampak Model Kooperatif STAD terhadap Hasil Belajar Pengukuran Panjang dan Berat Siswa Kelas III SDN H. Agus Salim - Alawi, Muhamad Alawi Abdurohim; Dek Ngurah Laba Laksana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This descriptive qualitative study investigates the implementation of the Student Teams Achievement Divisions (STAD) cooperative learning model in teaching length and weight measurement in a third-grade classroom at SDN H. Agus Salim, Bandung Regency. The study focuses on: (1) the design and enactment of STAD based lesson plans and learning tasks; (2) students’ social interaction and individual accountability within heterogeneous teams; and (3) trends in learning outcomes after the model is applied. STAD was implemented over three meetings through whole-class instruction, team work supported by concrete measuring tools and student worksheets, individual quizzes, improvement scores, and team rewards. Data were collected through participatory observation, semi-structured interviews with the teacher and six students, and document analysis of lesson plans, worksheets, and quiz records. Data were analyzed using the interactive model of data condensation, data display, and conclusion drawing with source triangulation. The findings show that STAD encourages more active participation, supportive peer communication, and clearer division of roles among team members. Average quiz scores and team improvement scores tended to increase, and most students achieved the minimum mastery criterion on measurement tasks. The study concludes that STAD is a promising model for strengthening meaningful social interaction while supporting conceptual understanding of length and weight measurement in lower primary mathematics. Keywords: STAD, Cooperative Learning, Social Interaction, Mathematics Achievement, Elementary Measurement ABSTRAK Penelitian deskriptif kualitatif ini mengkaji penerapan model pembelajaran kooperatif tipe Student Teams Achievement Divisions (STAD) pada materi pengukuran panjang dan berat di kelas III SDN H. Agus Salim, Kabupaten Bandung. Fokus penelitian meliputi: (1) perancangan dan pelaksanaan modul ajar berbasis STAD; (2) interaksi sosial dan akuntabilitas individu dalam tim heterogen; dan (3) kecenderungan hasil belajar setelah model diterapkan. STAD dilaksanakan dalam tiga pertemuan melalui presentasi kelas, kerja tim dengan dukungan alat ukur konkret dan LKPD, kuis individu, perhitungan skor perkembangan, dan penghargaan tim. Data dikumpulkan melalui observasi partisipatif, wawancara semiterstruktur dengan guru dan enam siswa, serta telaah dokumen berupa modul ajar, LKPD, dan rekap nilai kuis. Analisis data menggunakan model interaktif yang mencakup kondensasi data, penyajian data, dan penarikan kesimpulan dengan triangulasi sumber. Hasil penelitian menunjukkan bahwa STAD mendorong partisipasi yang lebih aktif, komunikasi sebaya yang suportif, dan pembagian peran yang lebih jelas di dalam tim. Rata-rata nilai kuis dan skor perkembangan tim cenderung meningkat, dan sebagian besar siswa mencapai Kriteria Ketuntasan Minimal pada tugas pengukuran. Penelitian ini menyimpulkan bahwa STAD merupakan model yang menjanjikan untuk memperkuat interaksi sosial bermakna sekaligus mendukung pemahaman konsep pengukuran panjang dan berat di kelas rendah sekolah dasar. Kata Kunci: STAD, Pembelajaran Kooperatif, Interaksi Sosial, Hasil Belajar Matematika, Pengukuran Panjang Dan Berat